Identification and Profiling of MicroRNAs During Embryogenesis in the Red Claw Crayfish Cherax quadricarinatus - Wang, Yan; Wang, Baojie; Shao, Xuqing; Liu, Mei; Jiang, Keyong; Wang, Mengqiang; Wang, Lei (Frontiers in Physiology, 2020)
MicroRNAs (miRNAs) are endogenous small non-coding RNAs that constitute a broad layer of gene regulation at both transcriptional and post-transcriptional levels from prokaryotes to eukaryotes. In embryonic development, they regulate the complex gene expression associated with the complexity of embryogenesis. However, the information of miRNAs in the red claw crayfish (Cherax quadricarinatus), an important commercial species and a potential biological model, is still rare. In the present study, miRNAs and their target genes were identified during three embryonic developmental stages of C. quadricarinatus. Nineteen known miRNAs and 331 novel ones belonging to 50 miRNA families were obtained. A total of 113 differentially expressed miRNAs were identified, and 2,575 target genes were predicted, of which 1,257 were annotated. Additionally, 63 target genes of 9 miRNAs in C. quadricarinatus were found to be related to embryonic development. For example, miR-10 and its target genes may regulate the nervous system development and body segmentation. MiR-2788 may regulate cell proliferation to impact embryonic development. Moreover, miR-28 (target gene tutl), miR-50 (target gene fbx5), and miR-1260b (target gene sif) may co-regulate eye development of C. quadricarinatus embryonic. These miRNAs together with their target genes constitute a network for regulating the development of tissues and organs in the embryo of C. quadricarinatus, and our results would lay a foundation for further study on the fundamental molecular and developmental mechanism of crustacean embryogenesis.